2014
DOI: 10.3906/sag-1205-17
|View full text |Cite
|
Sign up to set email alerts
|

Determining torsion angle of humerus head using MRI method

Abstract: Plant tissue culture is an efficient technique for conserving endemic plant species. A reproducible in vitro regeneration protocol was developed for the endemic Iris sari and Iris schachtii in the present study. The highest number of shoots per explant was obtained on Murashige and Skoog (MS) medium supplemented with 0.5 mg/L thidiazuron (TDZ) plus 0.5 mg/L α-naphthaleneacetic acid (NAA) and 1 mg/L TDZ plus 0.5 mg/L NAA, whereby 96.88% and 100% shoot induction with 9.55 and 11.34 shoots per explant of Iris sar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
(38 reference statements)
0
7
0
2
Order By: Relevance
“…The 3D measurement method employed in the present study is a strength because it eliminates projection errors inherent with 2D studies. 2,4,5,7,8,10,41,42 Also, clinical relevance was improved by basing the coordinate systems on common clinical landmarks and replication of the surgical humeral head osteotomy technique. Limitations included uncertain hand dominance and an imbalance of left–right arms in the female group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 3D measurement method employed in the present study is a strength because it eliminates projection errors inherent with 2D studies. 2,4,5,7,8,10,41,42 Also, clinical relevance was improved by basing the coordinate systems on common clinical landmarks and replication of the surgical humeral head osteotomy technique. Limitations included uncertain hand dominance and an imbalance of left–right arms in the female group.…”
Section: Discussionmentioning
confidence: 99%
“…6 Additionally, sex has been suggested to be a factor, although there is no consensus within the literature. [3][4][5]7,8 Traditionally, version has been measured with two dimensional (2D) computed tomography (CT) slices or radiographic images. [9][10][11][12] This has been shown to introduce errors as a result of a lack of standardized landmarks, as well as out-of-plane patient positioning that may cause projection errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1) Numerous studies have investigated the degree of humeral head retroversion by using various methods (e.g., direct anatomic measurements, radiography, computed tomography [CT], magnetic resonance imaging [MRI], ultrasonography, and computer-assisted methods). 1 5 6 7 8 9) Some studies demonstrated that retroversion of the proximal part of the humerus can be reliably measured on CT scans. 1 10) On CT scans, the orientation of the humeral head is defined as the perpendicular axis of the boundaries of the articular surface determined by using the limits of the subchondral bone in the largest circle of the humeral head.…”
mentioning
confidence: 99%
“…Aber auch der Nachweis mittels bildgebender Verfahren ist problematisch. Prinzipiell stehen als bildgebende Verfahren zur Bestimmung der Humerustorsion aktuell die Röntgendiagnostik, das MRT, das CT und die Sonographie zur Verfügung (Smith 1960;Graham 1967;Debevoise et al 1971;Dowd und Hopcroft 1979;Dähnert und Bernd 1986;Hindman et al 1988;Söderlund et al 1989;Fuchs et al 1991;Harland et al 1991;Kunz et al 1993;Ito et al 1995;Hernigou et al 2002;Tellioğlu et al 2014).…”
Section: Messung Der Humerustorsionunclassified